Customer satisfaction of online apparel businesses in Malaysia: point-purchase and post-purchase comparison - Noorshella Che Nawi; Abdullah Al- Mamun (Inderscience Online, 2017)
Increasingly, customer satisfaction has been viewed as being critical to the success of online businesses, with the growing understanding that customer satisfaction is the key to sustain the marketplace especially for online apparel businesses in Malaysia. This study intends to identify how factors influence Malaysian customers' online shopping satisfaction from the perspective of total online shopping experience, and its applications in the Malaysian e-retailing industry. This study develops a model for measuring customer satisfaction at different purchase phases: phase 1: exploratory study, phase 2: at point-of-purchase and phase 3: post-purchase. Complete data was collected from 268 respondents at the point-purchase phase and 154 respondents at the post-purchase phase. Findings of this study indicate that the mediating role of overall satisfaction on relationships between e-service quality and attitude towards the website are significant. Findings also noted a significant difference in overall satisfaction of items between point-of-purchase and post-purchase for all respondents. This study, therefore, suggests that the Malaysian e-retailing industry should create incentive programs to capture new customers or to retain existing ones. They should also consider the post-purchase phase by providing customers with better service on delivery and post-sales customer service.